RASA1 inhibits the progression of renal cell carcinoma by decreasing the expression of miR-223-3p and promoting the expression of FBXW7 - Zhang, Rui-Li (Biosci Rep, 2020)
RAS p21 protein activator 1 (RASA1), also known as p120-RasGAP, is a RasGAP protein that functions as a signaling scaffold protein, regulating pivotal signal cascades. However, its biological mechanism in renal cell carcinoma (RCC) remains unknown. In the present study, RASA1, F-box/WD repeat-containing protein 7 (FBXW7), and miR-223-3p expression were assessed via quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and Western blot. Then, the targeted correlations of miR-223-3p with FBXW7 and RASA1 were verified via a dual-luciferase reporter gene assay. CCK-8, flow cytometry, and Transwell assays were implemented independently to explore the impact of RASA1 on cell proliferation, apoptosis, migration, and cell cycle progression. Finally, the influence of RASA1 on tumor formation in RCC was assessed in vivo through the analysis of tumor growth in nude mice. Results showed that FBXW7 and RASA1 expression were decreased in RCC tissues and cell lines, while miR-223-3p was expressed at a higher level. Additionally, FBXW7 and RASA1 inhibited cell proliferation but facilitated the population of RCC cells in the G0/G1 phase. Altogether, RASA1 may play a key role in the progression of RCC by decreasing miR-223-3p and subsequently increasing FBXW7 expression.